Adversariality and Argumentation - Casey, John (Informal Logic)

(untitled) (Informal Logic, 2020)
The concept of adversariality, like that of argument, admits of significant variation. As a consequence, I argue, the question of adversarial argument has not been well understood. After defining adversariality, I argue that if we take argument to be about beliefs, rather than commitments, then two considerations show that adversariality is an essential part of it. First, beliefs are not under our direct voluntary control. Second, beliefs are costly both for the psychological states they provoke and for the fact that they are causally related to our actions. As a result, argument involving agreement can also be understood to be adversarial.